DAYA TARIK SEKTORAL, KARAKTERISTIK INDIVIDU, SERTA KESESUAIAN PILIHAN PEKERJAAN DAN PRODUKTIVITAS PEKERJA - - Susilo (Journal of Indonesian Applied Economics, 2009)
The purpose of this study is to analyze the effect of sectoral effort factor, individualcharacteristic and  job choice compability  to  labor productivity  in agriculture andmanufacture  sector at East  Java. Using Structural Equation Modeling--SEM withAMOS (Analysis of Moment Structural) Application Program to analyze the surveyresult. The result shows that sectoral effort factor and individual characteristic havesignificant effect to labor productivity in agriculture and manufacturing sectors, whilejob choice compability doesn’t have significant effect to labor productivity. It meansthat sectoral effort factor and individual characteristic effects to labor productivityin agriculture dan manufactur  sector doesn’t pass  through  job choice compability(intervening variable), but, it directly passes to labor productivity. Beside, this studycould prove that labor productivity in agriculture sector higher than labor produc-tivity manufacturing sector.Keywords:  Sector effort  factor,  individual characteristic, job choise compability,labor productivity